Integrated multi‐omics analysis supports role of lysophosphatidylcholine and related glycerophospholipids in the Lotus japonicus–Glomus intraradices mycorrhizal symbiosis. (27th October 2015) - Vijayakumar, Vinod; Liebisch, Gerhard; Buer, Benjamin; Xue, Li; Gerlach, Nina; Blau, Samira; Schmitz, Jessica; Bucher, Marcel
Abstract: Interaction of plant roots with arbuscular mycorrhizal fungi (AMF) is a complex trait resulting in cooperative interactions among the two symbionts including bidirectional exchange of resources. To study arbuscular mycorrhizal symbiosis (AMS) trait variation in the model plant Lotus japonicus, we performed an integrated multi‐omics analysis with a focus on plant and fungal phospholipid (PL) metabolism and biological significance of lysophosphatidylcholine (LPC). Our results support the role of LPC as a bioactive compound eliciting cellular and molecular response mechanisms in Lotus . Evidence is provided for large interspecific chemical diversity of LPC species among mycorrhizae with related AMF species. Lipid, gene expression and elemental profiling emphasize the Lotus–Glomus intraradices interaction as distinct from other arbuscular mycorrhizal (AM) interactions. In G. intraradices, genes involved in fatty acid (FA) elongation and biosynthesis of unsaturated FAs were enhanced, while in Lotus, FA synthesis genes were up‐regulated during AMS. Furthermore, FAS protein localization to mitochondria suggests FA biosynthesis and elongation may also occur in AMF. Our results suggest the existence of interspecific partitioning of PL resources for generation of LPC and novel candidate bioactive PLs in the Lotus–G. intraradices symbiosis. Moreover, the data advocate research with phylogenetically diverse Glomeromycota species for a broader understanding of the molecular underpinnings of AMS. Abstract : In research on arbuscular mycorrhizal symbiosis (AMS) development, relatively little is known about the contribution of lipids and lipid metabolism to cellular functions. With this work, we widen the fascinating avenues that lipid‐mediated processes in arbuscular mycorrhizal (AM) research harbour and offer. Integrated multi‐omics (lipidome, transcriptome and ionome) analysis in AMs discerns interspecific variation in lipid composition and biosynthesis and supports the role of lysophosphatidylcholine and other related glycerophospholipids in the Lotus japonicus–Glomus intraradices mycorrhizal symbiosis.